The Effect of Pharmacist Homecare Services on Medication Adherence, Drug-Related Problems, Clinical Outcomes, and Quality of Life of Hypertensive Patients at Sei Mencirim Public Health Center - Dimas Fragilie; Aminah Dalimunthe; Khairunnisa Khairunnisa (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Hypertension is one of the most prevalent chronic diseases in Indonesia (25.8%) and remains a leading cause of death globally, accounting for approximately three million deaths annually. Poor patient adherence to antihypertensive therapy continues to be a major challenge in achieving optimal blood pressure control and preventing cardiovascular complications. Objective: This study aimed to analyze the effect of pharmacist-led homecare interventions on medication adherence, drug-related problems (DRPs), clinical outcomes, and quality of life among hypertensive patients at Sei Mencirim Primary Health Center. Methods: A pre- and post-cohort study was conducted involving 38 hypertensive patients aged over 55 years between April and June 2024. Medication adherence was assessed using the MASES-R (Medication Adherence Self-Efficacy Scale-Revised) questionnaire, DRPs were identified according to the PCNE V9.0 classification, clinical outcomes were evaluated through blood pressure measurements, and quality of life was measured using the SF-36 (Short Form-36) questionnaire. Data were analyzed using the Wilcoxon Signed Rank test. Results: The majority of respondents were female (76.3%) and aged 56–66 years (71.0%). The mean adherence score significantly increased from 16.29 ± 2.35 to 40.97 ± 10.03 (p < 0.001), with adherence rates improving from 0% to 76.3%. A significant reduction was observed in drug-related problems, dropping from 14 to 2 cases, while adverse drug reactions decreased from 18 to 4 cases. The patients’ systolic blood pressure declined from 166.13 ± 17.85 mmHg to 129.07 ± 5.39 mmHg, and diastolic pressure decreased from 86.28 mmHg to 79.26 mmHg (p < 0.001). Furthermore, the average quality-of-life scores increased across all dimensions, including physical function (19.74–87.76), general health (2.19–90.46), and social functioning (4.28–94.41). Conclusion: Pharmacist-led homecare interventions involving continuous education, counseling, and patient support were proven effective in significantly improving medication adherence and quality of life among hypertensive patients. These findings suggest that such interventions should be implemented routinely in primary healthcare settings.